AGE-RELATED OUTCOMES IN PRIMARY PERCUTANEOUS CORONARY INTERVENTION (PPCI) (Journal of Medical & Health Sciences Review, 2025)
Background: Age plays a critical role in determining outcomes of Primary Percutaneous Coronary Intervention (PPCI) among patients presenting with ST-segment elevation myocardial infarction (STEMI). Variations in vascular pathology, collateral circulation, and comorbidities between younger and older patients can influence procedural success and recovery.Objective: This study aims to comprehensively evaluate age-specific differences in clinical presentation, procedural characteristics, and in-hospital outcomes among patients undergoing PPCI.Methods: A retrospective, comparative observational analysis was conducted using data from 426 patients who underwent PPCI. Patients were divided into two cohorts: Early Age (=60 years). Variables assessed included symptom duration, door-to-balloon (D2B) time, SYNTAX score (pre- and post-intervention), hospital stay, in-lab complications, TIMI flow, residual disease status, and in-hospital major adverse cardiac events (MACE).Results: Older patients demonstrated significantly longer D2B times, elevated post-PCI SYNTAX scores, higher prevalence of residual disease and pulmonary edema, and more frequent use of post-PCI GPIIb/IIIa inhibitors. Despite these differences, in-lab mortality was absent in both groups.Conclusion: Age is associated with more complex coronary anatomy and higher procedural challenge. Although mortality was not different, the older group experienced more residual disease and complications. Findings emphasize the need for tailored interventional approaches in elderly patients undergoing PPCI.